Moby-Dick - Needle, Jan. (Candlewick Press, 2006)
An abridgement of the nineteenth-century novel in which a young seaman joins the crew of the whaling ship Pequod whose fanatical Captain Ahab is in determined pursuit of the white whale Moby Dick.